Perceptions of farmers from the southern Brazil on the legislation to Protect Riparian Vegetation - Pfeifer, Fernanda Jéssica (2022)
Areas of riparian vegetation are considered by the Native Vegetation Protection Law (NVPL) (Law 12.651/2012) as Permanent Preservation Areas (PPAs). This study seeks to identify the perceptions of farmers in southern Brazil about LPVN and its importance relevance in the conservation of riparian vegetation. The study was developed in the state of Rio Grande do Sul, involving 90 farmers residing in the Atlantic Forest biome and 90 in the Pampa biome. We conducted data collection by applying semi-structured interviews, emphasizing LPVN and riparian vegetation recovering techniques. We then submitted all data to a process of content and statistical analysis. Most farmers (86.11%) affirm to know the rules/guidelines established by LPVN. This statement is greater among farmers who have higher education and more land. For 49.4% of farmers the legislation is important to rule population actions and thus maintain ecosystem services; however The study was developed in the state of Rio Grande do Sul, involving 90 farmers residing in the Atlantic Forest biome and 90 in the Pampa biome ever, they disagree with the established footage, due to economic factors. They highlight the importance of riparian vegetation recovering practices, by planting seedlings, especially those with the potential to generate financial benefits. They ignore the differences between native and exotic species for the recovering of riparian vegetation.